eCM 2016
DOI: 10.22203/ecm.v031a11
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cell responses to hydrostatic pressure and shear stress

Abstract: The effects of mechanical stimuli to which cells are exposed in vivo are, at best, incompletely understood; in this respect, gene-level information regarding cell functions which are pertinent to new tissue formation is of special interest and importance in applications such as tissue engineering and tissue regeneration. Motivated by this need, the present study investigated the early responses of human mesenchymal stem cells (hMSCs) to intermittent shear stress (ISS) and to cyclic hydrostatic pressure (CHP) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 51 publications
2
39
0
Order By: Relevance
“…Previous studies have shown that pressures of ,100 kPa were shown to up-regulate bone markers, such as Runx2, Osterix, distal-less homeobox 5, msh homeobox 2, and bone morphogenetic protein 2, under both static and dynamic regimes (8,9). In contrast, hMSCs stimulated with 10-100 kPa under 2 Hz regime were found to express no changes in mRNA expression of boneassociated markers (45). One significant difference between these studies is the use of osteogenic biochemical induction medium, which has been previously shown to modulate the mechanically induced osteogenic response (46).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that pressures of ,100 kPa were shown to up-regulate bone markers, such as Runx2, Osterix, distal-less homeobox 5, msh homeobox 2, and bone morphogenetic protein 2, under both static and dynamic regimes (8,9). In contrast, hMSCs stimulated with 10-100 kPa under 2 Hz regime were found to express no changes in mRNA expression of boneassociated markers (45). One significant difference between these studies is the use of osteogenic biochemical induction medium, which has been previously shown to modulate the mechanically induced osteogenic response (46).…”
Section: Discussionmentioning
confidence: 92%
“…When considered, the nature of anatomical progression from cortical to cancellous bone and the repetitive load-bearing function of this tissue would hypothesize as much. To investigate these ends, intermittent shear stress and cyclic hydrostatic pressure have been shown to elicit mechanosensitive gene profiles in MSCs and further work has shown enhanced production of bone ECM using pulsatile versus fixed hydrostatic shear flow [112, 113]. Interestingly, high acoustic frequencies will also guide MSCs toward osteogenesis and spare the adipogenic induction seen at lower frequencies [114], and larger three-dimensional pore size will elicit more osteogenic differentiation [111].…”
Section: Regenerative Goalsmentioning
confidence: 99%
“…Therefore, if inherent biomaterial characteristics are known, FSS can be calculated and applied via the respective flow velocity. Also, HP is a physiologic mechanical force that was shown to have several effects on stem cell behavior [Becquart et al, 2016]. It is commonly accepted that the in vivo HP in mammalian bone lies within the range of 10.7-120 mm Hg [Gurkan and Akkus, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on chondrogenesis and osteogenesis found diverse effects of HP probably due to differing experimental setups [Steward and Kelly, 2015]. However, HP was shown to enhance cellular viability and osteogenic differentiation [Huang and Ogawa, 2012;McGowan, 2014;Becquart et al, 2016].…”
Section: Introductionmentioning
confidence: 99%